"Filhos de abrigo": adoção tardia de crianças no Espírito Santo, 2009-2019 - Mergar, Stella Scantamburlo de (2020)
Considering the studies on the childhood and children adoption, this dissertation investigates the hypothesis that children over 06 years old are ignored, stigmatized for their ages on adoptive processes. For the analysis, we consider determinant the soci